Ethnic differences in the Prevalence of Thyroid disorders among population of Far Western Region of Nepal - Pandeya, Dipendra Raj; Bhatt, Mahendra Prasad; Bhatta, Mahesh Prakash; Bhattarai, Janardhan (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Thyroid disorder is second most common endocrine disorder after diabetes in the world. The burden of thyroid diseases in the general population is enormous especially in females. The aim of this paper is to study the prevalence of thyroid disorders among population of Far Western Region. Methods: The present work was conducted to study the pattern of thyroid disorders among different ethnic groups attended to the LifeCare Diagnostics and Research Center Pvt. Ltd. Dhangadhi. Total of 1000 patients suspected with thyroid disorders were enrolled in this study. The incidence of thyroid disorders and its relationship with the different ethnic, age groups and gender were investigated. Results: Out of 1000 patients with suspected thyroid dysfunction, 65.8% were euthyroid followed by 13.8 % of patients having subclinical hypothyroidism, 9.5% hypothyroidism, 7.9% hypothyroidism. The incidence subclinical hyperthyroidism 3.0% was lowest. Hypothyroidism was the most common thyroid disorders among ethnic groups, Chhetri 37.97% and Brahmin 40.57%. In addition, females were most affected among the population. Conclusion: The prevalence of thyroid disorders in Far western population showed difference among different ethnic group. Public awareness of thyroid disorders and their potential complications could lead to improved diagnostic and therapeutic facilities.